Cyberviolence - Graham, Roderick (Cybercrime and digital deviance, 2024)
The focus of this chapter is cyberviolence - a concept that entails such offenses as flaming, trolling, hate speech, cyberstalking and cyberbullying. Though resulting in a great deal of mental, physical, and emotional harm, cyberviolence can often go overlooked in cybercrime discourse. The various offenses falling under cyberviolence can have a number of cascading effects, as shown with hate speech and its association with discriminatory behavior, unfair social policies, and even genocide. Legislation against such activities, and especially where young people are targeted, has been steadily developing in recent years, with prosecutorial efforts similarly increasing. However, children and adults alike experience cyberviolence, and this chapter demonstrates that clearly.